Упростите выражение: 1) 7х ( х - 4 ) - х ( 6 - х ); 2) 5аb ( 4а + 3b ) - 10а ^2 ( 2b - 4...

0 голосов
62 просмотров

Упростите выражение:
1) 7х ( х - 4 ) - х ( 6 - х );
2) 5аb ( 4а + 3b ) - 10а ^2 ( 2b - 4 );
3) ху ( 2х - 11у ) - х ( ху + 14у^2 );
4) 5с^3 ( 4с - 3 ) - 2с^2 ( 8с^2 - 12 ).
Помогите пожалуйста!


Алгебра (109 баллов) | 62 просмотров
Дан 1 ответ
0 голосов
1) 7х ( х - 4 ) - х ( 6 - х ) = 7х2 – 28х – 6х + х2 = 8 х2 -34х = 2х(4х-17) - вот это, возможно, не обязательно
2) 5аb ( 4а + 3b ) - 10а ^2 ( 2b - 4 ) = 20а2 b +15 аb2 - 20а2 b + 40 а2 = 15 аb2+ 40 а2 = 5а (3b2+ 8а )
3) ху ( 2х - 11у ) - х ( ху + 14у^2 ) = 2 х2у - 11у2 х - х2у - 14у2 х = х2у - 25у2 х =
ху (х - 25у)
4) 5с^3 ( 4с - 3 ) - 2с^2 ( 8с^2 - 12 ) = 20с4 - 15 с3 - 16 с4 + 24с2 = 4с4 - 15 с3 + 24с2 =
с (4с3 - 15 с2 + 24с)
(1.1k баллов)
0

Ты лучшая!!!! Люблю!!!